PRINCIPALS QUALITY ASSURANCE PRACTICES IN THE MANAGEMENT OF SECONDARY SCHOOLS IN ANAMBRA STATE - Manafa, Ifeyinwa F.; Ihuarulam, Maryjane O. (UNIZIK Journal of Educational Management and Policy, 2019)
This study investigated the extent of implementation of quality assurance practices in the management of secondary schools in Anambra State. Three research questions guided the study. Descriptive research design was adopted for the study. A total of 153 prinigbozuruikecipals and 3,259 teachers from the three education zones out of the six in Anambra State constituted the population. Out of this number 44 principals and 264 teachers were sampled using proportionate stratified random sampling technique. A 20 item self-constructed questionnaire was used to elicit information from the respondent. Data collected were analyzed using mean score and standard deviation. The findings of the study showed that principals do not maintain and provide adequate infrastructures and that most principals exhibit poor leadership skills as they fail to enforce discipline in their schools. Based on the findings recommendations were made, which include among others that principals should maintain and provide adequate infrastructure and to adequately motivate teachers.